Employing Lactam Copolymerization Strategy to Effectively Achieve Pure Organic Room‐Temperature Phosphorescence in Amorphous State. Issue 23 (11th September 2019) - Wang, Disen; Yan, Ziang; Shi, Mingyu; Dai, Jinghong; Chai, Qiongjie; Gui, Huiqiang; Zhang, Yaopeng; Ma, Xiang
Abstract: Pure organic, amorphous room‐temperature phosphorescent (RTP) materials have aroused great attention because of their easy preparation and wide applications. Herein, several metal‐free, amorphous, lactam phosphorescent copolymers are prepared. Copolymers of N ‐vinylpyrrolidone (NVP) and N‐ vinylcaprolactam (NVCL) with small amounts of monomers exhibit diverse RTP emissions. The rigid polymer matrices of poly( N‐ vinylpyrrolidone) (PVP) and poly( N‐ vinylcaprolactam) (PNVCL) effectively help to inhibit nonradiative transition process of phosphors, which enhances the RTP emission. Furthermore, outstanding biocompatibility, low cost, and highly hydrophilic character make these PVP‐ and PNVCL‐based RTP copolymer materials potentially applicable in various fields. Abstract : A series of pure organic, amorphous copolymers exhibiting room‐temperature phosphorescence are prepared via simple radical binary copolymerization of N‐ vinylpyrrolidone and N‐ vinylcaprolactam with small amounts of monomers exhibit diverse emission properties. Easy preparation, low cost, highly hydrophilic character, and outstanding biocompatibility make these phosphorescent copolymers potentially applicable in a wide range of fields.